2007
DOI: 10.1186/1476-7120-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term echocardiographic follow up of left ventricular function with permanent right ventricular pacing in pediatric patients with and without structural heart disease

Abstract: BackgroundChronic right ventricular apical pacing may have detrimental effect on left ventricular function and may promote to heart failure in adult patients with left ventricular dysfunction.MethodsA group of 99 pediatric patients with previously implanted pacemaker was studied retrospectively. Forty-three patients (21 males) had isolated congenital complete or advanced atrioventricular block. The remaining 56 patients (34 males) had pacing indication in the presence of structural heart disease. Thirty-two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…We found 6 studies, 2,10,12,15,17 including the present study, where the definition of DCM was acceptably transparent and unequivocal, with a total of 54 patients meeting the criteria and 38 males vs 16 females had developed DCM. In our study, 7 of 9 patients developing LV dysfunction were males.…”
Section: Discussionmentioning
confidence: 94%
“…We found 6 studies, 2,10,12,15,17 including the present study, where the definition of DCM was acceptably transparent and unequivocal, with a total of 54 patients meeting the criteria and 38 males vs 16 females had developed DCM. In our study, 7 of 9 patients developing LV dysfunction were males.…”
Section: Discussionmentioning
confidence: 94%
“…In the near future, endocardial pacing in the systemic ventricle may become feasible through the application of ‘wireless pacing’. However, in practice, the routine transvenous approach seems justifiable in young adults, as RV apical pacing is well tolerated by most patients 10 31…”
Section: Discussionmentioning
confidence: 99%
“…Also the percentage of dilated cardiomyopathy developed after pacemaker implantation in our series is comparable to that of previously published studies. [7][8][9][10] Of interest, in our study, comparing patients who showed deterioration of left ventricular global systolic function during the follow-up and those who were stable, the only significant difference was a prepacemaker implantation LVSF more than 39%. This finding is in agreement with both pediatric and adult studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, starting the stimulation early and for a longer period could increase the risk of deterioration of left ventricular systolic function in these patients. Unfortunately, data on the long-term effect of right ventricular pacing in children and adolescents are still debated, [7][8][9][10][11][12][13] probably because of the different methodological criteria (isolated CAVB vs. CAVB associated with other complex congenital heart diseases; follow-up duration; lack of preimplant echo data; echocardiographic assessment performed by different readers; sample size).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation